Learning with the test : adapting encoding strategies to the retrieval requisites - Marques, Pedro André Ribeiro (2017)
Tese de doutoramento, Psicologia (Psicologia Cognitiva), Universidade de Lisboa, Faculdade de Psicologia, 2017